Capital crimes [large type] - Kellerman, Jonathan (Random House Large Print : Distributed by Random House, 2006)
When California state representative Davida Grayson is murdered, detectives Will Barnes and Amanda Isis must unravel her complex life to catch the murderer. Meanwhile, in Nashville, detectives Baker Southerby and Lamar Van Gundy must find out who slashed the throat of Jack Jeffries, rock legend, who had just come out of retirement to do a benefit.